Halal Malaysia brand equity mishap: false recognition of brand mere recognition using implicit association test - Wan Ismail, Wan Rusni; Othman, Mohhidin; Abdul Rahman, Russly; Kamarulzaman, Nitty Hirawaty; Ab Rahman, Suhaimi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Brand mere recognition is the fundamental step in the brand awareness and the first hurdle that any brand need to achieved before brand equity can come into the picture. Thus, consumers’ ability to recognize brand through its symbol or logo is very crucial and despite of its significant it is considered to be the lowest order in brand equity assessment but it does reveal the initial clue on how well the brand is performing in the market. Consumers ability to recognized the right Halal logo is also important to protect themselves against false logo that still plaguing Malaysian market. Therefore, this study will test on how well consumers able to identify the right Halal Malaysia brand using Halal semiotic cues. This study is an exploratory in nature using true experimental design methodology and implicit association test (IAT) as the measurement tool. A total of 33 Malay Muslim respondents participated in this experiment where respondents are required to response to the stimulus that consist of various Halal logo and response time are recorded and analyse according to the IAT procedure. Findings from this study clearly showed that there is a hesitation in response when facing the current Halal Malaysia logo which provide a clear indication of lack of mere recognition for this brand. In reality mere recognition is very important because it help consumers to choose the right product with the right Halal endorsement. Unfortunately the proliferation of other Halal logos that flooded the market consists of both recognized and unrecognized logo by JAKIM often adopted similar logo design strategy only add to the confusion. Clearly, the findings on Halal Malaysia logo mere recognition also revealed that there are some problems during the transition of old JAKIM Halal logo and current logo where the information related to new logo failed to reached targeted audiences.